Productivity-adjusted life-years and correlates of uncontrolled hypertension at two health facilities in Zambia. - Joreen P Povia; Sepiso K Masenga; Benson M Hamooya; Yordanos Gebremeskel (PLoS ONE)
Background Hypertension has in the recent past surfaced as one of the conditions that has a significant impact on workforce productivity in emerging economies. Zambia is no different and has in the recent past recorded increasing cases. Despite the impact of hypertension being of great importance in regards to productivity, we have scarcity of data and studies on hypertension-related Productivity-Adjusted Life-Years (PALYs) in Zambia and Africa at large. This study assessed the impact of hypertension on PALYs lost and socioeconomic factors associated with nonadherence to antihypertensive medication (NATAM). Methods This was a cross-sectional study of 198 participants from Livingstone University Teaching Hospital and Maramba Clinic situated in Livingstone, Zambia. Structured questionnaires were used to collect data. Productivity index multiplied by years lived was used to calculate PALYs and descriptive statistics were used to summarize sociodemographic, clinical and economic variables. Multivariable logistic regression was used to determine factors associated with NATAM. Results The participants had a median age (interquartile range (IQR)) of 49 years (41, 59) and 60.1% (n = 119) were females while 39.9% (n = 79) were male. Our estimated PALYs lost per person due to hypertension were 0.2 (IQR 0.0, 2.7). Cumulative PALYs value lost due to the burden of hypertension was estimated to be at $871,239.58 in gross domestic product (GDP). The prevalence of NATAM was 48% (n = 95). The factors that were significantly associated with NATAM were age (odds ratio (OR) 0.94; 95% confidence interval (CI) 0.90, 0.98), female sex (OR 2.52; 95%CI 1.18, 5.40), self-employment (OR 2.57; 95%CI 1.02, 6.45) and absenteeism from work (OR 3.60; 95%CI 1.16, 11.22). Conclusions Findings in our study highlight a high economic loss of PALYs due to hypertension with a potential to impact GDP negatively. We also found that NATAM reduced productivity and income among individuals of working age further impacting PALYs lost due to hypertension. The factors associated with NATAM were age, sex, employment status and absenteeism from work. This study underscores the need for interventions targeting young people, females, self-employed individuals, and absentees at work to improve adherence to antihypertensive drugs in order to reduce PALYs lost due to hypertension.